2014
DOI: 10.1044/2014_jslhr-h-13-0132
|View full text |Cite
|
Sign up to set email alerts
|

Gap Detection in School-Age Children and Adults: Effects of Inherent Envelope Modulation and the Availability of Cues Across Frequency

Abstract: Purpose The present study evaluated the effects of inherent envelope modulation and the availability of cues across frequency on behavioral gap detection with noise-band stimuli in school-age children. Methods Listeners were normal-hearing adults and 5.2- to 15.6-year-olds. Stimuli were continuous bands of noise centered on 2000 Hz, either 1000 or 25 Hz wide. In addition to Gaussian noise at these bandwidths, there were conditions using 25-Hz-wide noise bands modified to either accentuate or minimize inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 45 publications
6
24
2
Order By: Relevance
“…Although previous studies have not measured gap detection as a function of the bandwidth of LFN, studies using a narrowband (25-Hz-wide) LFN stimulus reported gap detection thresholds that were substantially lower than for random noise (Grose et al, 2008;Buss et al, 2014). This result is in accord with other studies indicating that gap detection performance is limited by inherent fluctuations of the noise, and is also consistent with the concept of modulation masking (e.g., Houtgast, 1989;Glasberg and Moore, 1992;Moore et al, 1993).…”
Section: Introductionsupporting
confidence: 81%
“…Although previous studies have not measured gap detection as a function of the bandwidth of LFN, studies using a narrowband (25-Hz-wide) LFN stimulus reported gap detection thresholds that were substantially lower than for random noise (Grose et al, 2008;Buss et al, 2014). This result is in accord with other studies indicating that gap detection performance is limited by inherent fluctuations of the noise, and is also consistent with the concept of modulation masking (e.g., Houtgast, 1989;Glasberg and Moore, 1992;Moore et al, 1993).…”
Section: Introductionsupporting
confidence: 81%
“…However, previous studies have shown that behavioral GDTs measured in school-aged children with normal hearing for broadband noise range from 5-10 ms (Buss et al, 2014; Amaral & Collella-Santos, 2010; Shinn et al, 2009; Trehub et al, 1995; Zaidan & Baran, 2013) and subjects with ANSD had longer GDTs than normal-hearing listeners (Michalewski et al, 2005; Zeng et a., 1999; 2005). In addition, only one subject (S15) among these eight subjects showed an objective GDT of 10 ms.…”
Section: Discussionmentioning
confidence: 92%
“…Although gap detection is widely used as a measure of temporal resolution, thresholds of adult listeners depend on the spectral and temporal characteristics of the stimuli bounding the gap (e.g., Eddins, Hall, & Grose, 1992;Grose, Buss, & Hall, 2008). A recent study by Buss, Hall, Porter, and Grose (2014) argued that the development of adultlike gap detection may, likewise, depend critically on spectral and temporal features of the stimulus. The ability to detect a gap in a spectrally wide stimulus was argued to mature earlier in childhood than the ability to detect a gap in low-fluctuation narrowband noise.…”
mentioning
confidence: 99%
“…One motivation for evaluating these stimulus features is that signal detection in quiet matures later in childhood for brief low-frequency stimuli than for high-frequency or long-duration stimuli (He, Buss, & Hall, 2010;Trehub, Schneider, Morrongiello, & Thorpe, 1988). Another motivation for evaluating frequency and ramp duration is that effects related to these features have bearing on the interpretation of gap detection data reported by Buss et al (2014). Buss et al (2014) evaluated gap detection in schoolage children and adults for a band of Gaussian noise that was either 25 or 1000 Hz wide.…”
mentioning
confidence: 99%
See 1 more Smart Citation